2013
DOI: 10.4067/s0716-97602013000300006
|View full text |Cite
|
Sign up to set email alerts
|

Lipids, proteins, phenolic composition, antioxidant and antibacterial activities of seeds of peanuts (Arachis hypogaea l) cultivated in Tunisia

Abstract: Fatty acid composition of peanut seed oil in four varieties cultivated in Tunisia showed that linoleic (C18:2), oleic (C18:1) and palmitic (C16) acids account for more than 84% for Chounfakhi and Massriya and for more than 85% of the total fatty acids of Trabilsia and Sinya seed oil respectively. Seed oil contents were signifi cantly diff erent (P ≤ 0.05) and did not exceed 48%. The study of total phenolics revealed that Chounfakhi contained more total phenolics (2.1 mg GAE/g DW), followed by the Massriya and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 33 publications
0
42
1
4
Order By: Relevance
“…2012, Sebei et al 2013, Naz et al 2014) e ainda se ligam aos sais biliares e colesterol no tubo digestivo, impedindo sua absorção e prevenindo, portanto, eventos ateroscleró-ticos (Pereira & Cardoso 2012). Essas propriedades justificam a redução nos níveis de triglicerídeos nos grupos com intervenção, ou seja, por adição de extrato de amendoim em comparação às dietas normolipídica e hiperlipídica, em que os animais não receberam extrato de amendoim.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…2012, Sebei et al 2013, Naz et al 2014) e ainda se ligam aos sais biliares e colesterol no tubo digestivo, impedindo sua absorção e prevenindo, portanto, eventos ateroscleró-ticos (Pereira & Cardoso 2012). Essas propriedades justificam a redução nos níveis de triglicerídeos nos grupos com intervenção, ou seja, por adição de extrato de amendoim em comparação às dietas normolipídica e hiperlipídica, em que os animais não receberam extrato de amendoim.…”
Section: Resultsunclassified
“…Indicando a tendência de melhor controle de peso para os animais suplementados com o extrato, ou seja, esse alimento poderá vir a ser um aliado na perda de peso e doenças cardiovasculares. Alguns pesquisadores relatam que o consumo de amendoim 5 vezes por semana (cerca de 155g / semana) também reduziu o risco de morte por doenças coronárias em 35% (Sebei et al 2013, Naz et al 2014.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…The content of monounsaturated fatty acids of the baru almond analyzed in the present study is higher than that found by Togashi & Sgarbieri 16 , 44.5 g/100 g. This difference may be related to several factors, such as genetic and environmental variations; therefore, it deserves further studies on the characterization of this fruit according to the region of origin. Investigating different peanut cultivars, Sebei et al 17 found total monounsaturated fatty acid values lower than those observed in this study, ranging from 31.31 to 38.79 g/100 g. Oleic acid content found in the cerrado cashew nut was similar to that of traditional cashew nut and close to that of olive oil (from 61.77 to 74.90 g/100 g) 18 , which is the main dietary source of this fatty acid.…”
Section: Discussionmentioning
confidence: 76%
“…Phenolic compounds included flavonoid compounds have many effects such as antioxidant, antibacterial, and antidiabetic activities [1][2][3][4]. Phenolic compounds are commonly used as a subject in many researches.…”
Section: Introductionmentioning
confidence: 99%